PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN JURANG UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG MATEMATIKA PESERTA DIDIK DI KELAS II MIN 1 GRESIK - Amirotul Insiyyah; Nur Hudah; Ria Resti Fauziah; Muhammad Luthfi Efendi (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research is motivated by the low arithmetic ability of class II students at MIN 1 Gresik, especially in addition and subtraction materials. The main causes are monotonous learning methods and lack of utilization of learning media. The purpose of this development research is to develop the Ravine Board Learning Media to improve the mathematical arithmetic ability of students in Elementary Schools/Islamic Elementary Schools. Based on these problems, researchers are motivated to design more active, creative, and easy-to-understand learning by involving all students in the learning process in class II of MIN Gresik, with a focus on the following problems: (a) The process of developing the ravine board media (b) The level of validity of the ravine board media development, (c) The level of practicality of the ravine board media development, (d) The effectiveness of the ravine board media development product. This study uses the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The subjects of the study were class II students of MIN 1 Gresik. Data were collected through expert validation, student response questionnaires, observations, and pretests and posttests. The results of the study showed that: The ravine board media was very feasible to use, with an average validation score of 57.5. The media was declared very practical with an average score of 91.5 from student responses. Students' numeracy skills increased from a pretest average of 67.5 (very poor category) to 82.3 (very good category). It can be concluded that the ravine board media has proven to be valid, practical, and effective in improving the numeracy skills of class II students, and is feasible to use in mathematics learning at MIN 1 Gresik.